1
$\begingroup$

let $a,b,c>0$ show that :$$(a^3+b^3+abc)^2(b^3+c^3+abc)^2(c^3+a^3+abc)^2-(a^2b+b^2c+c^2a)^3\cdot(ab^2+bc^2+ca^2)^3\ge 0$$Maybe there's some kind of identity in there.so I use wolfampha Calculated the results and found no identity. and the results are very complex. Maybe this inequality has a good solution.such as this following identity $$(x+y+z)(xy+yz+zx)=(x+y)(y+z)(z+x)+xyz$$

$\endgroup$
2
$\begingroup$

We need to prove that $$\prod_{cyc}\left(\frac{a^2}{bc}+\frac{b^2}{ac}+1\right)^2\geq\left(\sum_{cyc}\frac{a}{b}\right)^3\left(\sum_{cyc}\frac{a}{c}\right)^3.$$ Let $\frac{a}{b}=x$, $\frac{b}{c}=y$ and $\frac{c}{a}=z$.

Hence, $xyz=1$ and we need to prove that $$\prod_{cyc}\left(\frac{x}{z}+\frac{y}{x}+1\right)^2\geq(x+y+z)^3(xy+xz+yz)^3$$ or $$\prod_{cyc}(x^2+yz+zx)^2\geq(x+y+z)^3(xy+xz+yz)^3.$$ Now, since by AM-GM $$\sum_{cyc}x^4y^2=\frac{1}{6}\sum_{cyc}(4x^4y^2+y^4z^2+z^4x^2)\geq\sum_{cyc}x^3y^2z,$$ we obtain: $$\prod_{cyc}(x^2+yz+zx)=\sum_{cyc}(x^4y^2+x^3y^3+x^4yz+2x^2y^2z+3x^3z^2y+x^2y^2z^2)\geq$$ $$\geq\sum_{cyc}(x^3y^3+x^4yz+3x^3y^2z+3x^3z^2y+x^2y^2z^2).$$ Thus, it's enough to prove that $$\left(\sum_{cyc}(x^3y^3+x^4yz+3x^3y^2z+3x^3z^2y+x^2y^2z^2)\right)^2\geq(x+y+z)^3(xy+xz+yz)^3xyz.$$ Now, let $x+y+z=3u$, $xy+xz+yz=3v^2$ and $xyz=w^3$.

Hence, we need to prove that $$(27v^6-27uv^2w^3+3w^6+27u^3w^3-27uv^2w^3+3w^6+27uv^2w^3-9w^6+3w^6)^2\geq$$ $$\geq729u^3v^6w^3$$ or $f(u)\geq0,$ where $$f(u)=(v^6-uv^2w^3+u^3w^3)^2-u^3v^6w^3.$$ But $$f'(u)=2(v^6-uv^2w^3+u^3w^3)w^3(3u^2-v^2)-3u^2v^6w^3=$$ $$=2uw^6(u^2-v^2)(3u^2-v^2)+v^6w^3(3u^2-2v^2)\geq0,$$ which says that $f$ increases.

Thus, it's enough to prove $f(u)\geq0$ for a minimal value of $u$,

which happens for equality case of two variables.

Since the last inequality is symmetric and homogeneous, we can assume $y=z=1$,

which gives $$(x^4+8x^3+9x^2+8x+1)^2\geq(2x^2+5x+2)^3x.$$ Let $x^2+1=2tx$.

Hence, by AM-GM $t\geq1$ and we need to prove that $$(4t^2+16t+7)^2\geq(4t+5)^3$$ or $$(t-1)(4t^3+20t^2+38t+19)\geq0.$$ Done!

$\endgroup$
  • $\begingroup$ have you without uvw methods? $\endgroup$ – inequality May 3 '18 at 12:05
  • $\begingroup$ I have a proof by the uvw's technique, but it's a very complicated proof. $\endgroup$ – Michael Rozenberg May 3 '18 at 13:36

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.